Letter, 1946 Apr 29, St. Helena, Calif., to George Palmer Putnam, Lone Pine, Calif. - Sutton, S. (Purdue University Libraries, Archives and Special Collections, 1946)
Letter, S. Sutton to George Palmer Putnam, stating his beliefs that Earhart and Noonan were captured by the Japanese and Earhart was marooned west of Kerguelen, April 29, 1946